Pengaruh Brand Ambassador Dan Potongan Harga Terhadap Keputusan Pembelian Pada Layanan Jasa Transportasi Online Gojek Dengan Minat Beli Ulang Sebagai Variabel Intervening: Studi Kasus Pada Mahasiswa Universitas Diponegoro - Myken Flowrencia Sihaloho; Susilo Toto Raharjo (Diponegoro Journal of Management, 2026)
The transportation sector has undergone various phases of development, from conventional systems to services now accessible through mobile and digital platforms. Digital innovation has led to the emergence of online transportation services that offer greater ease of access, time efficiency, and broader accessibility for the wider community. Gojek, as one of the major players in Indonesia’s online transportation ecosystem, provides a variety of integrated application-based services, including mobility, food delivery, and other digital utilities. Amid intensifying competition in this industry and the growing adoption of online services, implementing strategic marketing initiatives has become essential for companies to attract consumers and maintain their loyalty, encouraging repeat purchases and thereby increasing sales volume. This study examines the influence of brand ambassadors and price discounts on the purchasing decisions of users of Gojek’s online transportation services, with purchase intention acting as an intervening variable. This study addresses inconsistencies in previous research on the impact of brand ambassadors on purchase intention, with some studies reporting significant positive effects while others report different findings. In addition, research on price discounts in online transportation services remains relatively limited. This finding consistently produced positive and significant findings across several of the variables examined. However, one relationship between variables was negative but not statistically significant. This result provides an opportunity for future research to further investigate the underlying factors. Moreover, the findings of this study are expected to support the development of more effective marketing strategies for companies in the online transportation service industry and enhance understanding of the factors that influence consumer purchasing decisions.